A framework for design information management system for architects - Muhammad Alhassan, Aliyu (2010)
Architectural design solutions are outcomes of information manipulations by designers. An activity in the architectural design process may require inputs from other phases. The architect must be able to keep track of the amount of information required to accomplish a design task, which is a difficult task to perform. A design information management system is required to assist designers with new ways of managing and handling design projects. Despite the difficulty of managing the information flows and the availability of tools and techniques that can assist in manipulating the flow, there is still a lack of research to better understand and manage these flows. Architectural design is characterised by rework (iteration). Many of the available process models are not capable of representing these iterative processes. The models that are capable of identifying iterations do not provide means for managing them. In this work, we review existing information system framework, information modelling tools and techniques, and propose an information system framework termed ADIMS based on web services to manage architectural design information. The work also addresses the problem of architectural design information management from the information flow perspective by introducing the design structure matrix as a modelling tool to aid in a better understanding and management of the flow of information within the RIBA work stages.